JILBAB DAN REPRODUKSI IDENTITAS PEREMPUAN KRISTEN RUANG PUBLIK SEKOLAH ACEH - Muhammad Ansor; Cut Intan Meutia (Universitas Gadjah Mada, 2016)
The article examined the experiences of Christian women teachers in the public space of school in Aceh.Based on the narrated biographies of seven teachers, this article focuses on exploring the regulationimpact of Islamic dress code toward formation of Christian women’s identity in Aceh. The source ofdata is collected through observation and semi-structured interviews during 2013- 2014. The articleuses the habitus theory from Bourdieu and the identity concept of ‘in between’ from Bhaba. This articleshows that the public space of school becomes the arena of power contestation between Moslem andthe minority, the Christian women, which led to the inclination of Christian women to wear headscraft.The article also shows that the implementation of Islamic sharia encourages the emergence of hybrididentity of the veiled Christian women. This hybrid identity was born from the result of complicatednegotiation between identities as women teacher, Christian, and citizen of Aceh.